Reading interest and reading pattern of rural library users in a low literacy rate area - Nor Aini Mohamed,; Shamsul Farid Samsuddin,; Hayrol Azril Mohamed Shaffril,; Jusang Bolong, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The rural library generates knowledgeable and up-to-date communities through the inculcation of positive lifestyles. The purpose of the study is to investigate reading interest and reading patterns among rural communities in the low literacy rate areas in Malaysia. The quantitative study employs a multi-stage cluster and simple random sampling, whereby 400 respondents from 16 rural libraries at Sabah, Sarawak, Kedah, and Kelantan were selected. This investigation shows that rural library users interested in the reading activity. Most of the users are female, read 2 to 5 books in a week, and prefer to read printed materials in Malay. There is no significant difference in reading interest and gender. Findings suggested that more library needs to be established in rural areas to foster reading culture. Librarians and community leaders play a role in promoting library facilities for the community. More research needs to be conducted to assess the impact of the rural library on the community, especially in the low literacy rate areas.